Quality Of Education And Competitiveness (Eurasian Research Bulletin, 2023)
The relevance of the topic of this article is determined by the increasing competition among the developing countries of the world and the fact that Uzbekistan follows a competitive strategy and strives to occupy high places in world rankings in various fields: economics, education, science, sports, information technology. The scientific article analyzes such concepts as "quality of education" and "competitiveness", studied the constituent elements of the quality of education, the impact of the quality of education on the formation of competitive competencies. At the same time, the constituent elements of competitive competencies were analyzed in relation to the higher education system. In conclusion, the idea is given that the quality of education is important in the formation and development of competitive competencies